Biting activity of Aedes scapularis (Rondani) and Haemagogus mosquitoes in Southern Brazil (Diptera: Culicidae) Atividade hematófaga de mosquitos Aedes scapularis (Rondani) e Haemagogus no sul do Brasil (Diptera: Culicidae) - Oswaldo Paulo Forattini; Almério de Castro Gomes (Universidade de São Paulo, 1988)
The biting activity of a population of Aedes scapularis (Rondani), Haemagogus capricornii Lutz and Hg. leucocelaenus (Dyar and Shannon) in Southern Brazil was studied between March 1980 and April 1983. Data were obtained with 25-hour human bait catches in three areas with patchy residual forests, named "Jacaré-Pepira", "Lupo" Farm, and "Sta. Helena" Farm, in the highland region of S. Paulo State (Brazil). Data obtained on Ae. scapularis were compared with those formerly gathered in the "Ribeira'' Valley lowlands, and were similar, except in the "Lupo" Farm study area, where a precrepuscular peak was observed, not recorded at the "Jacaré-Pepira" site or in the "Ribeira" Valley. In all the areas this mosquito showed diurnal and nocturnal activity, but was most active during the evening crepuscular period. These observations support the hypothesis about the successful adaptation of Ae. scapularis to man-made environments and have epidemiological implications that arise from it. As for Haemagogus, results obtained on the "Lupo" and "Sta. Helena" regions agree with previous data obtained in several other regions and show its diurnal activity. The proximity of "Lupo" Farm, where Hg. capricornii and Hg. leucocelaenus showed considerable activity, to "Araraquara" city where Aedes aegypti was recently found, raises some epidemiological considerations about the possibility of urban yellow fever resurgence. No período de março de 1980 a abril de 1983 foi estudada a atividade hematófaga de uma população de Aedes scapularis (Rondani), Haemagogus capricornii Lutz, Hg. leucocelaenus (Dyar e Shannon), na região sul do Brasil. Os dados foram obtidos com o emprego de isca humana, mediante captura de 25 horas de duração e correspondente a três áreas, contendo manchas de floresta residual, denominadas Jacaré-Pepira, Fazenda Lupo e Fazenda Santa Helena. Os resultados relativos a Ae. scapularis foram comparados com as coletas anteriormente feitas em áreas de planície da região do Vale do Ribeira e que revelaram comportamento semelhante, exceto na Fazenda Lupo, onde foi observado um pico pré-crepuscular que não foi registrado em Jacaré-Pepira ou no Vale do Ribeira. Em todas as áreas aquele mosquito demonstrou atividade diurna e noturna. Essas observações alicerçam a hipótese sobre a capacidade de adaptação de Ae. scapularis em ambiente alterado pelo homem e as implicações epidemiológicas daí decorrentes. Quanto a Haemagogus, os dados obtidos nas Fazendas Lupo e Santa Helena concordam com os primeiros resultados obtidos em diversas outras regiões, nas quais se revela o caráter diurno de sua atividade. Nas proximidades da Fazenda Lupo, onde Hg. capricornii e Hg. leucocelaenus mostraram considerável atividade, está a cidade de Araraquara, onde o Ae. aegypti foi recentemente encontrado, e assim cabem considerações epidemiológicas, sobre a possibilidade de ocorrência de febre amarela urbana.